Comparison of the removal of calcium hydroxide medicaments on the root canal treatment irrigated with manual and sonic agitation technique - Muryani, Anna; Hayati, Ayu Trisna; Adang, Rahmi Alma Farah (Universitas Padjadjaran, 2017)
Introduction: Irrigation of the root canal is an important part of the endodontic treatment. Root irrigation technique can be done with the manual and sonic system by using 2.5% NaOCI solution. Calcium hydroxide [Ca(OH)2 ] is used as a medicament for root canal sterilization. Root canal treatment will fail due to the imperfect removal of Ca(OH)2 residue. The objective of this research was to analyze the comparison of the removal of Ca(OH)2 medicaments on the root canal treatment irrigated with manual and sonic agitation technique using 2.5% NaOCI. Methods: The methods used in this study was experimental laboratory. The sample used was 30 maxillary incisors. The teeth were then divided into two groups randomly, then the root canal preparation was done by the crown down technique with irrigation using 2.5% NaOCI. The radicular part of the teeth was then split longitudinally, given a standardized groove in the one-third of the apical part, then applied with water-solved calcium hydroxide. The teeth were unified afterwards by using flowable composites, then soaked in the artificial saliva. The sample of the 1st group was irrigated by manual agitation technique, and the 2nd group by sonic agitation technique. The data results were analyzed by Kruskal-Wallis and Mann-Whitney tests. Results: The results of Ca(OH)2 removal were different between manual agitation technique compared to the sonic agitation technique. Conclusion: The irrigation using 2.5% NaOCl with the sonic agitation technique were proven to be more effective in removing Ca(OH)2 from root canals than the manual agitation technique.